Functional mechanisms of periodontium specific proteins in periodontal tissue regeneration - Li Chunwang; Yuan Meng; Wang Yawen; Li Yi; Shi Guanghuan (Guoji laonian yixue zazhi)
Periodontal tissue comprises a complex arrangement of soft and hard tissues essential for the physiological function of teeth. Numerous proteins in periodontal tissue are essential for maintaining its normal physiological function, while certain specific proteins are crucial for the homeostatic equilibrium and the development and remodeling of periodontal tissue. The identification of these particular proteins establishes a solid theoretical and practical foundation for addressing periodontal tissue diseases in the elderly and for the regeneration of periodontal tissue. This article examines the current research status of these specific proteins.